A globally converging algorithm for reactive robot navigation among moving and deforming obstacles. (April 2015) - Matveev, Alexey S.; Hoy, Michael C.; Savkin, Andrey V.
Abstract: We present a reactive strategy for the navigation of a mobile robot in dynamic a priori unknown environments densely cluttered with moving and deforming obstacles. Mathematically rigorous analysis of this law with the proof of its global convergence is provided; its performance is confirmed by computer simulations.